Towards sustainable and safe apparel cleaning methods: A review. (1st November 2016) - Troynikov, Olga; Watson, Christopher; Jadhav, Amit; Nawaz, Nazia; Kettlewell, Roy
Abstract: Perchloroethylene (PERC) is a compound commonly used as a solvent in dry cleaning, despite its severe health and environmental impacts. In recent times chemicals such as hydrocarbons, GreenEarth ®, acetal and liquid carbon dioxide have emerged as less damaging substitutes for PERC, and an even more sustainable water-based wet cleaning process has been developed. We employed a systematic review approach to provide a comprehensive overview of the existing research evidence in the area of sustainable and safe apparel cleaning methods and care. Our review describes traditional professional dry cleaning methods, as well as those that utilise solvents other than PERC, and their ecological attributes. In addition, the new professional wet cleaning process is discussed. Finally, we address the health hazards of the various solvents used in dry cleaning and state-of-the-art solvent residue trace analysis techniques. Highlights: PERC dry cleaning is being phased out due to its health and environmental risks. Most non-PERC dry-cleaning solvents pose similar health and environmental hazards. Professional wet cleaning of textiles is a safe and sustainable cleaning method. Wet cleaning's effectiveness in cleaning natural fibers must be established. Analysis of solvent residues on fabrics requires a combination of existing methods.